Longitudinal single-cell profiling reveals molecular heterogeneity and tumor-immune evolution in refractory mantle cell lymphoma - Shaojun Zhang (Nature Portfolio, 2021)
Mantle cell lymphoma can be refractory to treatment. Here, the authors used single cell sequencing to study the tumours of patients that were responsive and resistant to treatment and find gains of 17q in resistant tumours, which they attribute to increased expression of Birc5 and validate these findings in mouse models of the disease.